PERANAN KPU DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR TAHUN 2020 DI PROVINSI JAMBI - Muhsin Iwan Saputra; Irwandi Irwandi; Muhammad Eriton (Universitas Jambi, Fakultas Hukum, 2022)
This study aims 1) to find out what programs are carried out by the Jambi Province General Election Commission in increasing public participation in the 2020 Governor and Deputy Governor Elections; 2) To find out community participation in the Election of Governor and Deputy Governor in Jambi Province in 2020. The results show that the program carried out by the General Election Commission of Jambi Province in increasing public participation in the Election of Governor and Deputy Governor in Jambi Province in 2020 is socialization in the form of counseling ( face-to-face), socialization through print and electronic media, socialization of health protocols (simulation at TPS), socialization through the installation of socialization props and dissemination of socialization materials, organizer-based socialization and socialization using smart cars. Based on the results of interviews with respondents who were registered in the permanent voters (DPT) in the Election of Governor and Deputy Governor in Jambi Province in 2020 that all of them participated in the Election of Governor and Deputy Governor in Jambi Province in 2020.